MANAGEMENT MODEL FOR THE SUSTAINABILITY OF THE FISHERY RESOURCES IN THE GULF OF NICOYA, COSTA RICA - Pacheco-Urpí, Oscar P (2013)
The state of the management of fishery resources and management strategies for their sustainability are established in the Gulf of Nicoya. The model for sustainable fishing management in Gulf of Nicoya is constructed using approaches based on defined management strategies and on perceived needs and weaknesses. This model unfolds within the context of integral human development in hand with strategies for the conservation of fishery resources within the context of capacity development for compliance at all levels, transparency and participation, management of fishery resources, generate new sources of employment and production, and formation and training of the residents of this coastal zone.